A computer aided team analysis of the euro 2000 in soccer - Luhtanen, P.; Belinskij, A.; Häyrinen, M.; Vänttinen, T. (5th World Congress of Performance Analysis of Sport, 2001)
In international tournaments, teams are judged on their ability to win matches. Behind the wins, the teams must have effective ways to win the ball, create successful attacks first to reach the attacking third of the field, create effectively scoring chances and to complete them by scoring goals with a high efficiency. The purpose of this study was to study selected offensive and defensive variables of field players and goalkeepers in the EURO 2000 and to relate the results to the final team ranking in the tournament. All matches (n=31) of the EURO 2000 were recorded using video and analysed with computerised match analysis hardware and video playback system for game performance analysis using SAGE Game Manager for Soccer software. The quantitative (number of executions) and qualitative (percentage of successful executions) game performance variables were as follows: passes, receivings, runs with ball, scoring trials, interceptions, tackles, goals and goalkeeper's savings. The total and effective playing times were recorded and the game performance results were standardised for 90 minutes playing time. Team ranking in each variable was used as a new variable. The final ranking order in the WC '98 tournament was explained by calculating the rank correlation coefficients between team ranking in the tournament and ranking in the following variables: ranking of ball possession in distance, passes, receivings, runs with the ball, shots, interceptions, tackles and duels. Selected quantitative and qualitative sum variables were calculated using ranking order of all obtained variables, only defensive variables and only offensive variables. The means and standard deviations of the game performance variables were calculated. Ranking order in each variable was constructed. Spearman's correlation coefficients were calculated between all ranking game performance variables. The average to have the ball in possession in distance was 5,7 km. Holland was superior in ball possession in distance (8.9 km). During the 90 minutes the average amount of passes per team was 369 and the percentage of the successful passes was 78 %. Team's average number of receivings was 267 and the success per cent was 93 %. In this tournament the amount of the runs with the ball in a match was on average 38 per team and the percentage of the successful runs was 65 %. Shots and headers that lead to a goal scoring opportunity were on average 13 per team in a match. About 9 % of them lead to goal. This means 1.2 goals per team in a match. In this tournament, teams tried to intercept on average 113 times per match per team and the percentage of the successful interceptions was 95 %. The average number of tackles was 134 per team in a match. The percentage of successful tackles was 47 %. The goalkeepers and defenders made on average 3 savings each. In goal scoring opportunities, the goalkeepers saved with the percentage of 69 %. Spearman's correlation coefficients between the tournament ranking and the measured variables were as follows: percentage of the successful passes (r=1.00, p<.001), the percentage of successful goal scoring trials (r=.665, p<.01). The correlation coefficients of sum variable of all relative offensive success variables and all defensive and offensive variables were .633 (p<.01) and (.572, p<.05). The presented results showed that there was a variable of successful passes at team level that explained the success in the EURO 2000. France was the best team in the performance activity of passes, receivings, runs with ball and tackles. In percentage of the successful passes, France was the top team. The goalkeeper's saving percentage of was seventh best. The strengths of Italy were in defence. The Italians were best in interceptions and third best in tackles. In the passing activity their position was 15th, but in the percentage of successful passes 2nd. In the over all ranking taking into account all analysed variables, Italy was 13th. This analysis would give Holland a better place than third. Holland was 1st in ball possession (8.9 km) and 2nd in the amount of passes and shots and also close to the top place in the corresponding successful executions. Because Holland controlled the ball a lot, it didn't have many chances to interceptions or duels. This can be seen in the amount of interceptions and duels. Germany was traditionally strong in having the ball in possession (2nd), in passing play (2nd) and in the number of goal scoring trials ((4th). However, the weaknesses were found in defence activity of interceptions (16th) and tackles and duels (15th).